THE DYNAMIC EFFECTS OF OIL PRICE SHOCKS ON BANK DEPOSITS AND CREDIT IN IRAQ: A STRUCTURAL VAR APPROACH - Kawthar Kareem Abdul Razzaq (Scholar Express Journals, 2025)
The paper examines the dynamic behavior of oil price shocks with the bank deposits and the credit of Iraq with data coverage of 2004-2023 in a quarterly format. Based on a Structural Vector Autoregression (SVAR) machinery, the study observes the effects of the global oil prices dynamism on critical financial pointers in an oil-based economy. The findings indicate that positive oil shocks have short-term effect on bank deposits as more revenues through increased liquidity inflows are obtained by the government. But credit to the private sector reacts procyclicality, and shrinks after a shock in the short run, and then rebounds as fiscal spending is recycled through the economy. It is also revealed that the movement of oil price Granger-causes the movements in bank deposit and credit which supports the fact that they are predictive in financial sector in Iraq. The impulse response functions and the historical decomposition also show that oil shocks had a predominant role inducing financial activity especially in the moments when the price volatility was high. The paper ends with some policy proposals among which is stability in managements of oil revenue, bolstering of risk buffers in the banks and improved fiscal-monetary cooperation. These are the necessary steps to promoting financial strength and providing sustainable credit and deposit development in oil-dependent economies such as Iraq.
Keywords: Oil price shocks; Bank deposits; Credit to private sector